Repeated anaphylactic shocks during bee venom immunotherapy and successful continuation of treatment after vaccine change - Misarko, Aleksandra; Hejnosz, Aleksandra; Piwowarek, Krzysztof; Chciałowski, Andrzej (Alergologia Polska - Polish Journal of Allergology, 2025)
The study aims to investigate potential causes of repeated anaphylactic reactions during immunotherapy and to analyze possible measures to be taken in such a situation. The reported patient experienced an anaphylactic reaction after taking a maintenance dose of immunotherapy. Despite changing the antihypertensive drug from an angiotensin-converting-enzyme inhibitor, during an attempt to restart immunotherapy, another anaphylactic reaction occurred. Systemic mastocytosis was excluded. Implementing immunotherapy with a different vaccine was successful. In the case of generalized anaphylactic reactions occurring during immunotherapy, it is advisable to analyze what other drugs the patient is taking and, if suspected, perform testing for systemic mastocytosis. The tolerance of the second vaccine may have been due to the presence of an aluminum hydroxide adjuvant, which allows for a slower release of the allergen. In some cases, changing the immunotherapy vaccine may be crucial due to potential sensitivity to non-venom components.